Kebijakan dan Manajemen Pembiayaan Pendidikan - Amalia, Irdhatul; Basri, Basri; Siradjuddin, Siradjuddin; Suban, Alwan (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This research aims to outline the concept of education financing policy and management. This study uses qualitative research with a literature study research method. The data in this study come from relevant literature, books and journals related to the subject of this article. This study discusses several main problems, namely: 1) the concept of an effective and efficient financing system in education; 2) education budget and financial management; 3) the management system of financing for the implementation of education; 4) education financing models. After collecting data from several relevant literature, the data is researched, reviewed, described, developed and innovated from previous research. Education financing policy and management aims to create an efficient and effective system, as well as ensure access to quality education for each individual through optimal resource management. This aspect is very important because it has a direct effect on the quality of education. With clear regulations and good management, it is hoped that education financing can be managed in an effective way to improve the quality of education services at all levels.